Motivation, discipline and employee performance - Herudini Subariyanti; Andri Rizko Yulianto (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of motivation and discipline on employee performance. This research is a quantitative descriptive study using primary data sources taken directly from the employees of the company PT. Jaya Sutra Nusantara, as the source of research data. The independent variable consists of motivation and discipline, while the dependent variable is employee performance. The research design was a random sample study which was conducted on 211 samples of employees at PT. Jaya Sutra Nusantara, data collection techniques through questionnaires. Furthermore, the data were analyzed quantitatively by using statistical methods with the help of a computer program SPSS 22.00, with classical assumption test analysis techniques, simple correlation, multiple correlation, and basic assumption tests, partial correlation, multiple correlation, F test, t test, determination test. From the research results, it can be concluded that there is a positive and significant influence between work motivation and work discipline on employee performance at PT. Jaya Sutra Nusantara